2022
DOI: 10.3390/jpm12030454
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Response to Treatment with Glucagon-like Peptide 1 Receptor Agonists: Opportunities for a Tailored Approach to Diabetes and Obesity Care

Abstract: The available data suggest differences in the course of type 2 diabetes mellitus (T2DM) between men and women, influenced by the distinguishing features of the sex. Glucagon-like peptide 1 receptor agonists (GLP-1 RAs) are a relatively new class of antidiabetic drugs that act by mimicking the function of endogenous glucagon-like peptide 1. They constitute valuable agents for the management of T2DM as, in addition to exerting a strong hypoglycemic action, they present cardiorenal protective properties, promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 79 publications
6
42
0
Order By: Relevance
“…There is evidence that central GLP-1 effects could be modulated by sex steroids; e.g., female rats are more sensitive than males to the anorexigenic effect of a centrally administered GLP-1 receptor agonist. The anorexigenic effect of estrogen and modulation of GLP-1 activity could involve the ventral tegmental area (VTA) and the nucleus accumbens (NAc) [26,27]. Further studies are urgently needed to identify gender-related differences in efficacy and toxicity of GLP-1 RA in the pre-and post-bariatric population for a tailored approach to obesity management.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that central GLP-1 effects could be modulated by sex steroids; e.g., female rats are more sensitive than males to the anorexigenic effect of a centrally administered GLP-1 receptor agonist. The anorexigenic effect of estrogen and modulation of GLP-1 activity could involve the ventral tegmental area (VTA) and the nucleus accumbens (NAc) [26,27]. Further studies are urgently needed to identify gender-related differences in efficacy and toxicity of GLP-1 RA in the pre-and post-bariatric population for a tailored approach to obesity management.…”
Section: Discussionmentioning
confidence: 99%
“…Through mediation analysis, TSH had no mediating effect on sex and GISE, and possibly small sample size caused that. Some studies showed the apparent sex-specific differences in the frequency of GSEA partially attributed to higher exposures to liraglutide in females, possibly due to their lower average body weight ( 31 ) and the greater prevalence of functional GID among females ( 32 ). Therefore, it is necessary to take measures to prevent GSEA in women with type 2 diabetes treated with liraglutide.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting data on gender differences in incretin-treated patients emerged from a study that considered data from two Korean national databases, where females were about twice as likely as males to report adverse events related to the use of GLP-1 RA, with a reporting ratio M/F of 2.34. Adverse events were predominantly gastrointestinal upset and headache (the latter with a hazard ratio of 7.97), and no significant difference was found between the two sexes in episodes of nocturnal hypoglycaemia [ 170 , 171 ]. Regarding the effects on HbA1c, gender did not prove to be a predictor of a more or less significant reduction, unlike what emerged in several previous studies.…”
Section: Sex- and Gender-related Differences In The Management Of Chr...mentioning
confidence: 99%